A Present of their Past? Anthropologists, Native People, and their Heritage - Trigger, Bruce G. (Culture, 1988)
Most ethnology collections were made by anthropologists at a time when Native People were believed to be dying out. These collections were intended to allow future generations of anthropologists to study traditional Native cultures. Since then anthropologists have become interested in how Native People currently live. At present Native People are alienated both from the material vestiges of their past that are kept in museums and from anthropology, which remains the study of Native People by EuroCanadians. This alienation can in part be overcome by a program of affirmative action designed to secure employment for Native People as professional anthropologists and museum curators.